Development and Evaluation of a Portable Visual Stimulus Rebound Board for Table Tennis Training - Alit Rahmat; Reshandi Nugraha; Regi Dwi Septian; Muhammad Zaky Al Ghifary (Jurnal Pendidikan Terapan, 2026)
Purpose: This study aims to design, develop, and evaluate the feasibility of a visual stimulus based portable table tennis rebound board. This instructional media was developed to facilitate students' independent practice and help improve visual focus and stroke accuracy during table tennis lessons in schools. Methods: The research method used is Research and Development (R&D), referring to the 10 step Borg and Gall model. This study involved a sample of 76 participants selected through purposive sampling, divided into three progressive testing phases: (1) preliminary field testing on 6 students (n = 6), (2) main field testing on 30 students (n = 30), and (3) final operational field testing on 40 participants (n = 40) consisting of 12th grade students. Prior to the field trials, the media was evaluated by a validator panel comprising 4 experts (n = 4), namely 2 media/technical experts and 2 subject matter/instructional experts. Data were collected using a questionnaire instrument consisting of 20 statements on a 5 point Likert scale, alongside open ended feedback forms. Quantitative data were analyzed using descriptive percentages and standard deviation (SD), while qualitative data were analyzed through response frequency grouping. Findings: The application of a coordinated target area consisting of 12 target boxes with a high-contrast zig-zag design consistently improved the media's feasibility score across all stages. Quantitative assessment began with expert validation, yielding an average score of 78.75% (± 3.25%) from media/technical experts ("Feasible" category) and 83.50% (± 2.10%) from subject matter/instructional experts ("Highly Feasible" category). During the field trials, the feasibility percentage increased to 85.80% (± 2.45%) in the preliminary testing, rose to 89.60% (± 2.10%) in the main testing, and reached a peak of 92.40% (± 1.85%) during the final operational testing ("Highly Feasible" category). Overall, the media experienced a substantial total feasibility increase of Δ = +13.65% from the initial prototype to the final product, accompanied by an increasingly uniform distribution of responses. Furthermore, the analysis of open-ended feedback revealed that 87% of students in the main field testing (n = 30) confirmed that the color cues and alphanumeric coordinate codes significantly helped accelerate their visual focus and improve their stroke direction accuracy. Research Implications: This study provides an empirically validated instructional media reference for Physical Education teachers and sports practitioners, proving that the integration of structured visual cues into independent practice equipment effectively assists students in target aiming and enhances the overall effectiveness of table tennis learning in schools. Originality: The novelty of this research lies in the transformation of a conventional rebound board into an interactive training medium that combines dual-sided ball rebound with a high contrast alphanumeric target matrix, thereby integrating students' physical agility and cognitive focus engagement within a single independent practice tool.